Association between serum uric acid‐to‐high‐density lipoprotein cholesterol ratio and insulin resistance in patients with type 2 diabetes mellitus - Zhou, Xinhe; Xu, Jing (Journal of diabetes investigation, 2024)
ABSTRACT Introduction Previous studies have shown that the serum uric acid‐to‐high‐density lipoprotein cholesterol ratio (UHR) is related to metabolic syndrome. However, no existing study has examined the relationship between UHR and insulin resistance (IR). Therefore, this study aims to explore the association between the UHR and IR in patients with type 2 diabetes mellitus (T2DM). Methods Patients with type 2 diabetes mellitus (1,532 males and 1,013 females) were enrolled. Insulin resistance was measured by homeostatic model assessment of insulin resistance (HOMA‐IR) and was defined as HOMI‐IR ≥ 2.69. Pearson correlation, multiple logistic regression, ROC analysis, and subgroup analysis were used to evaluate the association between UHR and IR. Results UHR was associated with HOMA‐IR in patients with type 2 diabetes mellitus (pearson's correlation coefficient = 0.274 in males and 0.337 in females, P < 0.001). Multiple logistic regression analysis showed that UHR was significantly correlated with insulin resistance (OR = 1.06, 95%CI = 1.03–1.08 in males and OR = 1.11, 95%CI = 1.08–1.15 in females). The area under the ROC curve (AUC) of UHR (AUC = 0.665 for males and 0.717 for females, all P < 0.01) was the largest compared with that of UA and HDL‐C in insulin resistance. Subgroup analysis showed that there was a more significantly positive correlation among subjects with BMI ≥ 24 kg/m2, age < 60 years old, HbA1c < 7%, non‐hypertension, or in female subjects. Conclusion Elevated UHR is significantly correlated with insulin resistance, which can be used as an indicator of insulin resistance in patients with type 2 diabetes mellitus. UHR is positively correlated with an increase in HOMA‐IR and the risk of insulin resistance (IR) in a mass of patients with type 2 diabetes mellitus. UHR is more effective in detecting IR compared with uric acid or HDL‐C alone.